Komposisi Coleoptera Permukaan Tanah pada Pertanaman Markisa (Passiflora linguaris L.) di Desa Cubadak Kenagarian Air Dingin Timur Kecamatan Lembah Gumanti Kabupaten Solok - Ratna, Ratna; Jasmi, Jasmi; Safitri, Elza (STKIP PGRI Sumbar, 2013)
ABSTRACT The existing and crowded of the soil population in an area was really depend to the environmental factors. The cutting of Marquise leaf (Pasiflora linguaris L.) continuously makes the accumulation of decayed leafs to floor of the plants. It enables to live the soil insects, especially coleopteran. Meanwhile the process of yield by accumulating can broke the soil ecosystem which disturbing the existing of soil animals. This research aim to know the composition of Coleoptera on the soil surface to the plants of marquise (Pasiflora linguaris L.) at the village of Cubadak, East Air Dingin Area of Lembah Gumanti District in Solok Regency. The type of this research was survey descriptive. The research was executed from Augustus 2013 at the village of Cubadak, East Air Dingin Area of Lembah Gumanti District in Solok Regency. The collection of sample in the field used pitfall trap which used about 30 units to each stations. The placement of pitfall trap in the field used stratified sampling. Coleoptera on the soil surface was found on the plants of marquise (Pasiflora linguaris L.), those are 18 families consisted of 25 species. In the plants of marquise at the age 1 year old, found 12 families consisted of 18 species, while on the plants of marquise at the age 5 years old, found 9 families consisted of 5 species. The analysis of similarity index toward species of Coleptera on the soil surface revealed about the composition of Coleoptera to the plants of marquise at the age one years old with other at the age five years old have relative small similar. While the correlation analysis showed that the species of Coloeptera on the soil surface between the plants of marquise at the age one year old and five years old have sequence similar the composition of them. The observation to the environmental factors to the plants of marquise showed the air temperature was about 20,50 oC up to 20-25 oC, temperature of soil was about 18,91 oC up to 20-40 oC, soil humidity was about 1-2, pH of soil was 6,80-6,96.